2002
DOI: 10.1159/000063569
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenic Patients Who Develop Postoperative Confusion Have an Increased Norepinephrine and Cortisol Response to Surgery

Abstract: The purpose of this study was to investigate the relationship between postoperative confusion and the plasma norepinephrine (NE), adrenocorticotropin (ACTH) or cortisol response to surgery in schizophrenic patients. We studied 50 schizophrenic patients and 35 control patients who underwent orthopedic surgery and perioperatively measured plasma NE, ACTH and cortisol levels. Postoperative confusion during 72 h after the end of the operation occurred in 14 of 50 schizophrenic patients (28%) and in 2 of 35 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It is important to consider our results in the context of the current literature. Several reports [12][13][14][15][16][17][18][19][20][21][27][28][29][30][31][32][33] have examined associations between psychiatric comorbidity and surgical patient outcomes; however, it is difficult to in- fer valid conclusions because of the heterogeneity of the studies regarding the temporal relationship of psychiatric comorbidity identified (eg, psychiatric illness identified before or after surgical admission), type of psychiatric comorbidity studied, and types of outcomes considered.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to consider our results in the context of the current literature. Several reports [12][13][14][15][16][17][18][19][20][21][27][28][29][30][31][32][33] have examined associations between psychiatric comorbidity and surgical patient outcomes; however, it is difficult to in- fer valid conclusions because of the heterogeneity of the studies regarding the temporal relationship of psychiatric comorbidity identified (eg, psychiatric illness identified before or after surgical admission), type of psychiatric comorbidity studied, and types of outcomes considered.…”
Section: Commentmentioning
confidence: 99%
“…For example, in a study of pediatric trauma patients, Gaines et al 32 found that children with a preexisting psychiatric illness had increased ICU and overall hospital-related lengths of stay and were more likely to be discharged to a location other than home. Next, in a further series of studies, Kudoh et al [12][13][14][15][16][17][18][19] examined patients undergoing abdominal and orthopedic surgery and compared a number of outcomes (eg, pain responses to analgesic agents, postoperative psychosis or confusion after anesthesia, and rates of postoperative depression after anesthesia) in cohorts with or without depression or schizophrenia. None of these studies examined mortality as an outcome.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…BPRS 41Plasma cortisol 21.00Kaneda et al (2002)53Chronically medicated inpatients. Anxiety similar to controlsPlasma cortisol 06.00–07.00Kudoh et al (2002)50FGA treated, stable chronic SCHPlasma cortisol timed in relation to anaesthesia for orthopaedic surgeryShirayama et al (2002)28Neuroleptics. In and outpatients with an absence of positive sx.…”
Section: Resultsmentioning
confidence: 98%
“…We previously reported that chronic schizophrenic patients had decreased plasma cortisol response to surgical stress, 6 and the occurrence of postoperative confusion in schizophrenic patients is associated with an increase in plasma cortisol concentrations during and after surgery. 7 Thus, it may be important, in schizophrenic patients, to decrease plasma cortisol concentrations during and after surgery. Epidural administration of local anesthetics can attenuate elevation of secretion of cortisol.…”
Section: Introductionmentioning
confidence: 99%